Correlation between Ultrasound Findings of Uric Acid Precipitate in MTP I and Acute Gout Flare in Gouty Arthritis - SUSANTI, Elys; Ilyas, Muhammad; Idris, Nurlaily; Zainuddin, Andi Alfian; Murtala, Bachtiar; HP, Faridin (Jurnal Kedokteran Brawijaya, 2020)
Acute gout flare is the most common manifestation of gouty arthritis that intermittently occurs with severe pain in the joints due to interactions between monosodium urate crystals (MSU) and the surrounding tissues. The most common predilection is the metatarsophalangeal joint (the 1st MTP). Ultrasound examination is a modality that can be used to visualize MSU crystal precipitates in and around joints. This study aimed to determine the correlation between the findings of the MSU crystal precipitate on the 1st MTP using ultrasound with the occurrence of acute gout flare in gout patients. This study was an analytical observational study with a cross-sectional method. The samples were 41 patients with a history of previous acute flares and in the intercritical phase when participating in the study. Examinations of ultrasound on the 1st MTP and random serum uric acid level were performed. Evaluations were carried out on both of the 1st MTPs to assess the shape of the MSU crystalline precipitate, namely Double Contour Sign (DCS), aggregate, and tophus. Each sample was evaluated within five days to assess the presence or absence of an acute flare. The diagnostic tests used were the Chi-Square Test and the Fischer Exact Test with a significance value of p <0.05. The results showed the images of DCS were seen in 20 samples with 9 (45%) samples experiencing acute flare (p <0.05), while in 21 samples where no DCS were found, all did not experience any flare. Findings of aggregate and tophus were rarely found, 7.3% and 4.9%, respectively. In this study, the finding of DCS precipitates using ultrasound has a significant correlation to the emergence of acute flare and is a significant form of precipitate findings in this study, whereas aggregate and tophus precipitates are difficult to determine.